6(x+2)=3(2x+2)+6

Simple and best practice solution for 6(x+2)=3(2x+2)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+2)=3(2x+2)+6 equation:


Simplifying
6(x + 2) = 3(2x + 2) + 6

Reorder the terms:
6(2 + x) = 3(2x + 2) + 6
(2 * 6 + x * 6) = 3(2x + 2) + 6
(12 + 6x) = 3(2x + 2) + 6

Reorder the terms:
12 + 6x = 3(2 + 2x) + 6
12 + 6x = (2 * 3 + 2x * 3) + 6
12 + 6x = (6 + 6x) + 6

Reorder the terms:
12 + 6x = 6 + 6 + 6x

Combine like terms: 6 + 6 = 12
12 + 6x = 12 + 6x

Add '-12' to each side of the equation.
12 + -12 + 6x = 12 + -12 + 6x

Combine like terms: 12 + -12 = 0
0 + 6x = 12 + -12 + 6x
6x = 12 + -12 + 6x

Combine like terms: 12 + -12 = 0
6x = 0 + 6x
6x = 6x

Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 57-2x=10x+21 | | 4(3x-1)+6=5(2x-4) | | 4x+9=8x-12 | | 2(x+2)-3(x+3)=8 | | -6x^2-9x^2+15=0 | | x+8=-x-12 | | 0=4x^2+16x+45x+180 | | 3y=-2x+4 | | -16t^2+46t+4=0 | | x^6+56X^3-512=0 | | X^2+2x=115 | | 80-3x=15x+16 | | 6x-8=3x+11 | | 6-3(3x-1)=-27 | | x+80=3x+68 | | 10-8x=145-43x | | 7x-2y=56 | | 4x+2-3x-3=8 | | x^4+x^3-2x-2=0 | | 3x+2=9y | | 2d+8=28 | | 5x-5=2(3x-1)-2(x+3)+7 | | 9-4x=15-12x | | 18=4 | | 4+7x=6x-7 | | 5t+7=20 | | 70-5x=3x+18 | | 7x^2+x-3=0 | | 9-8x=55-22x | | 4x^2+61x+180=0 | | -15-11y=-9-3y | | 3(x+4)=2(2x-5)+13 |

Equations solver categories